2017
DOI: 10.1101/222554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of key pathways and metabolic fingerprints of longevity in C. elegans

Abstract: Impaired insulin/IGF-1 signaling (IIS) pathway and caloric restriction (CR) are two wellestablished interventions to prolong lifespan in worm C. elegans. However, a cross comparison of these longevity pathways using a multi-omics integration approach is lacking.In this study, we aimed to identify key pathways and metabolite fingerprints of longevity that are shared between IIS and CR worm models using a multi-omics integration approach. We generated transcriptomics and metabolomics data from two long-lived mut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
(36 reference statements)
3
6
0
Order By: Relevance
“…The gluconate shunt, the first reaction of which is mediated by Gcd1, provides NADPH and ribose 5‐phosphate through the pentose phosphate pathway . Although the genetic regulation of the NADPH‐generating pathways has not been well‐studied under nutrient starvation, some studies have described the relationship between genes involved in the pentose phosphate pathway and lifespan, suggesting that the transcription levels of pentose phosphate pathway genes are actively adjusted to maintain cell viability . Based on our additional ChIP‐Seq and RNA‐Seq results, we found that Rsv1 directly represses the transcription of idn1 , gnd1 , hxk2 , and gcd1 , a set of genes involved in the glucose shunt and pentose phosphate pathway, for up to 6 h of glucose starvation (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…The gluconate shunt, the first reaction of which is mediated by Gcd1, provides NADPH and ribose 5‐phosphate through the pentose phosphate pathway . Although the genetic regulation of the NADPH‐generating pathways has not been well‐studied under nutrient starvation, some studies have described the relationship between genes involved in the pentose phosphate pathway and lifespan, suggesting that the transcription levels of pentose phosphate pathway genes are actively adjusted to maintain cell viability . Based on our additional ChIP‐Seq and RNA‐Seq results, we found that Rsv1 directly represses the transcription of idn1 , gnd1 , hxk2 , and gcd1 , a set of genes involved in the glucose shunt and pentose phosphate pathway, for up to 6 h of glucose starvation (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Given this and in the hope of finding alternative compounds and/or targets for therapeutic interventions, we investigated how genetic inhibition of the IIS has lifespan-extending properties in OXPHOS-deficient organisms. Previously, xanthine along with adenine has been found to be slightly, yet significantly reduced in IIS-deficient nematodes within a larger context of metabolic flexibility (Gao et al, 2018). As part of our target validation, we then defined the epistatic relationship between the IIS cascade and novel molecular components predicted to participate in the metabolic reprogramming of mitochondrial mutant nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…PPARδ has also been observed in response to exercise [41]. The changes of the pathways, such as lipid metabolism, fatty acid degradation and metabolic pathways, have also been reported in CR [42,43]. Studies have reported that HF has an important impact on the lipid metabolism process in rat liver [44].…”
Section: Discussionmentioning
confidence: 95%